SURVEI SEROLOGIS TOXOPLASMOSIS PADA TERNAK KAMBING (Capra sp.) DENGAN METODE TOXOPLASMA MODIFIED AGLUTINATION TEST (To-MAT) DI DESA PURWOSARI, KECAMATAN METRO UTARA, KOTA METRO - S., Adryan Filly; R., Emantis; P., Gina Dania; S., Endah (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
Toxoplasmosis is a zoonotic disease caused by parasitic protozoa, Toxoplasma gondii. Transmission of toxoplasmosis can occur through direct infection, ie when humans eat meat from infected animals and are eaten half-cooked. Goats are one of the most half-cooked animals such as satay. In the city of Bandarlampung the prevalence of toxoplasmosis in goats circulating in the community reached 60%. This study aims to determine the prevalence and level of toxoplasmosis infection in goat livestock in Purwosari Village, Metro Utara. This research was conducted from November to December 2018. This type of research was descriptive using serological with the To-MAT (Toxoplasma Modified Aglutination Test) method. The result of the study found that in Purwosari, Metro Utara the prevalence of toxoplasmosis in goats circulating in the community reached 96,67%. Keywords: Capra sp., To-MAT Method, Toxoplasmosis